Osnovnye napravlenija razvitija psichologii sporta - Rodionov, A. V. (Teorija i Praktika fiziceskoj Kul'tury, 2003)
The aim of this article was to show the basic stages in the Russian sports psychology's development and the role of the All-Russia scientific research institute of physical culture in this process.